Short-term effects of increasing compost application rates on soil C and greenhouse gas (N2O and CO2) emissions in a California central coast vineyard - Wong, Connie T. F.; Falcone, Mia; Rich, Geovan; Stubler, Craig; Malama, Bwalya; Lazcano, Cristina; Decock, Charlotte (Frontiers in Environmental Science, 2023)
Compost application is commonly considered by winegrape producers to improve soil health while sequestering C and mitigating climate change. However, inputs of available C and nitrogen (N) as nutrients can induce emissions of greenhouse gases (GHG) such as carbon dioxide (CO2) and nitrous oxide (N2O). A two-year field experiment in a Mediterranean vineyard of the California Central Coast was conducted to investigate the short-term effects of compost application at four different rates on soil C dynamics and GHG emissions. Two years of GHG sampling were performed using static chambers at vineyard management events in two functional locations (tractor row and under the vines). Soil samples were collected annually in spring at the same locations at 0-15, 15-30 and 30-60 cm depth, and during GHG sampling at 0-15 cm. Increasing rate of compost application did not increase soil C stock, cumulative GHG emissions and global warming potential. The increase in active soil C observed to the depth of 60 cm suggesting that increasing compost application rate up to the rate of 13.5 Mg ha-1 year-1 can facilitate the early stages of C stabilization and sequestration. Compost application did not have a significant effect on grape yield or cover crop growth during the study. Our results provided important information on the potential environmental tradeoffs as GHG emissions from compost applications, which should be taken into account when considering vineyard C budget.